Segmentasi Pasar Jasa Pendidikan Menuju Era Society 5.0 - Anis Zohriah; Ahmad Qurtubi; Ahmad Fatoni (Peneliti.net, 2023)
The world is currently experiencing developments in science and technological sophistication that are very rapid which causes standards for various aspects of human life to be based on the demands of the times., directly proportional to the increasingly competitive competition in educational institution. This research was conducted to analyze the segmentation of the education services market towards the era society 5.0. The approach taken is descriptive qualitative with the method of library research. The method of collecting data is by exploring data techniques by reading, reviewing, and analyzing various relevant literature sources. Research results: 1) Efforts to increase the marketing of educational services towards the era of society 5.0, education managers must apply concepts in accordance with technological developments and continue to create innovations in accordance with consumer expectations. 2) Educational institutions must be able to identify potential customers based on domain characteristics to increase sales and educational services. 3) Market segmentation for educational services can be carried out using demographic, psychographic and geographical approaches. 4) Marketing approaches that can be applied are undifferentiated marketing, differentiated marketing, and centralized marketing. 5) Three needs to be an automatic digitization system in the process of using technology so that educational institutions can continue to exist.